2020
DOI: 10.1038/s41598-020-74337-w
|View full text |Cite
|
Sign up to set email alerts
|

Textile sensors platform for the selective and simultaneous detection of chloride ion and pH in sweat

Abstract: The development of wearable sensors, in particular fully-textile ones, is one of the most interesting open challenges in bioelectronics. Several and significant steps forward have been taken in the last decade in order to achieve a compact, lightweight, cost-effective, and easy to wear platform for healthcare and sport activities real-time monitoring. We have developed a fully textile, multi-thread biosensing platform that can detect different bioanalytes simultaneously without interference, and, as an example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 66 publications
2
46
0
Order By: Relevance
“…The textile pH sensor showed a normalized sensitivity of (7.5 ± 0.3) × 10 −3 pH −1 in the range 2–7, with no penalization of the sensing performance if compared to the rigid analogous fabricated on a glass substrate. The same functionalization strategy based on PEDOT:PSS/PEDOT:BTB was also adopted to design a thread pH sensor [ 83 ]. The textile sensor was capable of detecting pH selectively during simultaneous recordings in combination with another thread-based sensor for Cl − detection and will be discussed in the section entitled “Multi-sensing platforms”.…”
Section: Textile Chemical Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The textile pH sensor showed a normalized sensitivity of (7.5 ± 0.3) × 10 −3 pH −1 in the range 2–7, with no penalization of the sensing performance if compared to the rigid analogous fabricated on a glass substrate. The same functionalization strategy based on PEDOT:PSS/PEDOT:BTB was also adopted to design a thread pH sensor [ 83 ]. The textile sensor was capable of detecting pH selectively during simultaneous recordings in combination with another thread-based sensor for Cl − detection and will be discussed in the section entitled “Multi-sensing platforms”.…”
Section: Textile Chemical Sensorsmentioning
confidence: 99%
“…Recently, Possanzini et al [ 83 ] reported a fast, cost-effective and innovative strategy to fabricate a textile multi-sensor platform that merged a versatile and referenceless geometry structure with the robustness of a potentiometric-like transduction mechanism. The multi-thread sensing platform sketched in Figure 7 B i could stably measure pH ( Figure 7 B ii) and Cl − concentration ( Figure 7 B iii) simultaneously and selectively.…”
Section: Textile Chemical Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since textiles usually act as natural insulators, it is necessary for them to become conductive prior to electrodeposition. This is feasible by the creation of conductive layers (in a pre-treatment step) on a textile surface, using different metals, such as Ag [51,87], Cu, [88][89][90], Ni [91], Mxenes [92], Ni-Co selenide nanowires [93], NiMoO 4 /CoMoO 4 nanorods [94], LaMnO 3 /MnO nanoarrays, ZnO nanostructures deposited on an Ni-Cu-Ni conductive layer [95], and LiMn 2 O 4 [96], conductive polymers [97] or carbon-based materials [11,[22][23][24][25][26]. Schematic presentation of a typical electrochemical deposition process of a metallic layer onto PES fabric, using a three-electrode system, is shown in Figure 5a, where the deposition of Ni 3 Se 2 NPs is carried out on the conductive fabric (used as a working electrode), resulting in a metallic polyester layered fabric.…”
Section: Electrochemical Depositionmentioning
confidence: 99%
“…[ 98 ] Copyright 2021, John Wiley and Sons); ( b ) average resistance values of differently electroplated conductive threads (reprinted with permission from Ref. [ 97 ] Copyright 2021, Springer Nature Limited); ( c ) working principle of the thread sensor that detects chloride ions, pH and sweat simultaneously (reprinted with permission from Ref. [ 97 ] Copyright 2021, Springer Nature Limited); ( d ) SEM image of PET coated uniformly with amorphous NiWO 4 (adapted from Ref.…”
Section: Figurementioning
confidence: 99%